To find the equivalent expression, we need to simplify the expressions inside the parentheses, simplify any exponents, and then perform any remaining operations.
Using the order of operations:
1/2(9−7^0) = 1/2(9-1) = 1/2(8) = 4
(−29)^0 = 1
Therefore, the equivalent expression is:
4 + 1 = 5
None of the given options are equivalent to 5.
Which of the following is an equivalent expression to 1/2(9−7^0)+(−29)^0? (1 point)
Responses
1/2(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
1/2(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
1/2(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)+1
3 answers
retry
Apologies for the confusion.
To simplify the expression:
1/2(9-7^0)
= 1/2(9-1)
= 1/2(8)
= 4
(-29)^0
= 1
Now, the expression becomes:
4 + 1 = 5
Therefore, the equivalent expression is 5.
None of the given options are equivalent to 5.
To simplify the expression:
1/2(9-7^0)
= 1/2(9-1)
= 1/2(8)
= 4
(-29)^0
= 1
Now, the expression becomes:
4 + 1 = 5
Therefore, the equivalent expression is 5.
None of the given options are equivalent to 5.